Reproductive health and birth practices among early married females: A cross-sectional study in Jaipur India - Chaudhary, Chintu; Khan, Mohd. Najmul Aqib; Ahmad, Sameena (Asian Journal of Medical Sciences, 2022)
Background: Early marriage is not only a violation of females but also causes harm to their physical and psychological health.Aims and Objectives: The aim of the study was to determine the prevalence of early marriage and its association with reproductive health of females.Materials and Methods: This community based cross-sectional study was conducted among 322 married females in the field practice areas of JNU-IMRC, Jaipur, Rajasthan. The data were analyzed using Statistical Package for the Social Sciences 20.0.Results: The study found that 53.4% of the females had married before the age of 18 years. Significant associations were found between age at marriage, their socio-economic status, number of children, awareness of contraception, and history of various obstetric complications (P